Tectonic design of elastic timber gridshells - Fernandes, Jorge G. (2016)
This paper aims to 'bridge the gap' between engineers and architects for a better understanding of the design process of elastic timber gridshells. The purpose is to inspire architects to develop innovative timber structural forms informed by engineering knowledge. This paper is organised in two parts: the first part is a theoretical reflection on the concept of tectonic and on the combined application of architectural and structural knowledge; the second part is dedicated to the review and definition of the various decisions and consequences during the design and construction of elastic timber gridshells.